Do FIGO Stage IA and Small (⩽2 cm) IB1 Cervical Adenocarcinomas Have a Good Prognosis and Warrant Less Radical Surgery?. Issue 2 (1st February 2012) - Al-Kalbani, Moza; McVeigh, Gerard; Nagar, Hans; McCluggage, W. Glenn
Abstract : Objectives: There is a controversy regarding the optimal management of small cervical adenocarcinomas, and more radical surgery is often undertaken compared to similar size squamous carcinomas. We wished to determine the risk of parametrial involvement and metastatic disease and the outcome in International Federation of Gynecology and Obstetrics (FIGO) stage IA and small (⩽2 cm) stage IB1 cervical adenocarcinomas. Methods: All women with a diagnosis of International Federation of Gynecology and Obstetrics stages IA1, IA2, or IB1 cervical adenocarcinoma with a maximum tumor size of 2 cm were identified between 1999 and 2010 in Northern Ireland. A single pathologist reviewed all pathology prospectively at a cancer center tumor board. Results: A total of 74 women were identified (mean age, 39 years; range, 25–72 years). In total, 36 women had stage IA1, 9 women had stage IA2, and 29 women had stage IB1 cervical adenocarcinomas. Surgical treatment ranged from local excision (cone or large loop excision of transformation zone) to radical hysterectomy and pelvic lymph node dissection; adjuvant therapy was not administered in any case. No parametrial involvement was seen in the 36 women who underwent parametrial resection. No lymph node metastasis was identified in the 45 women who underwent pelvic lymph node dissection. Lymphovascular space invasion was identified in 6 cases. No tumor recurrence or metastasis was noted during a mean follow-up of 35 months. Conclusions: The optimal management of women with IA or small IB1 cervical adenocarcinoma is controversial, and radical surgery is often undertaken. Our data suggest that there is an extremely low risk of parametrial and lymph node involvement with tumors 2 cm or smaller and a low recurrence rate. Less radical surgery may be warranted for small cervical adenocarcinomas, and this should be addressed by future studies.